Facing It AIDS Diaries and the Death of the Author - Chambers, Ross (University of Michigan Press, 1998)
For a generation or more, literary theorists have used the metaphor of "the death of the author" in considering the observation that to write is to abdicate control over the meanings one's text is capable of generating. But in the case of AIDS diaries, the metaphor can be literal. Facing It examines the genre not in classificatory terms but pragmatically, as the site of a social interaction. Through a detailed study of three such diaries, originating respectively in France, the United States, and Australia, Ross Chambers demonstrates that issues concerning the politics of AIDS writing and the ethics of reading are linked by a common concern with the problematics of survivorhood.